Peranan Kebijakan Obat dalam Memperbaiki Keterjangkauan Obat - Yusi Anggriani (Fakultas Farmasi Universitas Pancasila, 2018)
Medicine is a pharmaceutical product that has imperfect market characteristics. This affects affordability to the community, and therefore it is necessary for the government to regulate medicine prices. Medicine prices can be regulated in the medicine supply chain by the industry, importers, distributors and health facilities such as pharmacies, hospitals and medicine sellers. Developed and high income countries generally regulate the prices of medicines and are part of a health insurance system. In contrast with the situation in developed countries, medicine pricing regulation in developing countries and Lower Middle Income Countries is not well established. The regulation of mark-ups in distribution channels is the most common strategy used by LMIC. Small country with only a few pharmaceutical facilities has a weak bargaining position, generally the government cannot set prices. The application of cost-plus pricing is quite effective if it is implemented in a small country. In developing countries with a large market segment and adequate pharmaceutical industry facilities the price competition method is an effective strategy option to get lower prices. In practice, the application of medicine pricing policy is dynamic. The medicine pricing system in a country can be changed or combined with other methods if the evaluation does not provide optimal results or generates unintended impacts.